Identification of the Extradural and Intradural Extension of Pituitary Adenomas to the Suprasellar Region: Classification, Surgical Strategies, and Outcomes - Yang, YouQing; Bao, YouYuan; Xie, ShenHao; Tang, Bin; Wu, Xiao; Yang, Le; Wu, Jie; Ding, Han; Li, ShaoYang; Zheng, SuYue; Hong, Tao (Frontiers in Oncology, 2021)
Abstract Objective Suprasellar pituitary adenomas (PAs) can be located in either extradural or intradural spaces, which impacts surgical strategies and outcomes. This study was to determine how to distinguish these two different forms of PAs and analyzed their corresponding surgical strategies and outcomes. Methods We retrospectively analyzed 389 patients undergoing surgery for PAs with suprasellar extension (SSE) between 2016 to 2020 in our center. PAs were classified into two main grades according to tumor topography and their relationships to the diaphragm sellae (DS) and DS-attached residual pituitary gland (PG). Grade 1 tumors were located extradurally and further divided into grades 1a and 1b, while grade 2 were located intradurally. Results Of 389 PAs, 292 (75.1%) surrounded by a bilayer structure formed by the DS and the residual PG were classified into grade 1a, 63 (16.2%) with lobulated or daughter tumors resulting from the thinning or even absence of the residual PG and subsequently rendering the bilayer weaker were classified into Grade 1b, and the residual 34 (8.7%) PAs which broke through the DS or traversed the diaphragmic opening and encased suprasellar neurovascular structures were classified into Grade 2. We found that the GTR of suprasellar part of grade 1a, 1b, and 2 decreased with grading (88.4%, 71.4%, and 61.8%, respectively). The rate of major operative complications, including CSF leakage, hemorrhage, and death, increased with grading. Conclusions Identifying whether PAs with SSE are located extradurally or intradurally is essential, which depends on whether the bilayer structure is intact. PAs with an intact bilayer surrounding structure were classified as grade 1. These were extradural and usually had good surgical outcomes and lower complications. PAs with no bilayer structure surrounding were classified as grade 2. These were intradural, connected to the cranial cavity, and had increased surgical complications and a lower rate of GTR. Different surgical strategies should be adopted for extradural and intradural PAs.